Self-evaluation with a view to the accreditation of the career in Libraries and Documentation - Miranda Arguedas, Alice (2006)
This paper describes the way in which developed the self-assessment process with a view to the accreditation of the School of Library and Information Science from 1999-2004, based on the "Accreditation Manual" National Accreditation System, SINAES . The criteria taken into account are related to: Academic Personnel, Curriculum, Students, Administration, Infrastructure and Equipment and Impact and Relevance. It seeks to ensure process quality to students, graduates, employers and national and international society.